2021
DOI: 10.1039/d0py01515f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, aqueous solution behavior and self-assembly of a dual pH/thermo-responsive fluorinated diblock terpolymer

Abstract: The synthesis of fluorinated dual-responsive block terpolymers via sequential reversible addition-fragmentation chain transfer (RAFT) polymerization is presented. The resulting block terpolymers consist of a hydrophobic block which comprises an alternating...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…While fluoropolymers oftentimes exhibit outstanding hydrophobicity and chemical inertness, the incorporation of gem -CF 3 /OH could dramatically improve the hydrophilicity and pH responsiveness due to decreased p K a of hydroxyls, as influenced by the strong electron-withdrawing geminal CF 3 substituents. Such materials are highly interesting for applications as chemically amplified and pH-responsive polymeric materials . Taking PCF 3 VB- co -PVAc copolymers as examples (Figure A), when silicon surfaces were coated with PCF 3 VB- co -PVAc of different fractions of gem -CF 3 /B ( F CF 3 VB = 0.49 in Figure B, F CF 3 VB = 0.79 in Figure C), two substrates exhibit similar contact angles for water (85 and 86°).…”
Section: Investigations On Water Contact Anglesmentioning
confidence: 99%
“…While fluoropolymers oftentimes exhibit outstanding hydrophobicity and chemical inertness, the incorporation of gem -CF 3 /OH could dramatically improve the hydrophilicity and pH responsiveness due to decreased p K a of hydroxyls, as influenced by the strong electron-withdrawing geminal CF 3 substituents. Such materials are highly interesting for applications as chemically amplified and pH-responsive polymeric materials . Taking PCF 3 VB- co -PVAc copolymers as examples (Figure A), when silicon surfaces were coated with PCF 3 VB- co -PVAc of different fractions of gem -CF 3 /B ( F CF 3 VB = 0.49 in Figure B, F CF 3 VB = 0.79 in Figure C), two substrates exhibit similar contact angles for water (85 and 86°).…”
Section: Investigations On Water Contact Anglesmentioning
confidence: 99%
“…Recently, Falireas et al reported the synthesis of dual pH-/temperature-responsive fluorinated block copolymers based on an alternating poly­(VAc- alt -2-trifluoro­methacrylic acid) sequence and poly­(DMA) and poly­( N -isopropyl­acrylamide) (PNIPAM) blocks (Scheme ).…”
Section: Sequence Regulation In Synthetic Fluoropolymersmentioning
confidence: 99%
“… a (a) Preparation of alternating poly­(MAF-TBE- alt -VAc) macroCTA; (b) hydrolysis of poly­(MAF-TBE- alt -VAc) into poly­(MAF- alt -VOH); (c) synthesis of poly­(MAF-TBE- alt -VAc)- b -PDMA; (d) obtained poly­(MAF-TBE- alt -VAc)- b -PNIPAM; and (e) hydrolysis of poly­(MAF-TBE- alt -VAc)- b -PNIPAM into P­(MAF- alt -VOH)- b -PNIPAM. Reproduced with permission from ref . Copyright 2021 Royal Society of Chemistry. …”
Section: Sequence Regulation In Synthetic Fluoropolymersmentioning
confidence: 99%
“…They however readily copolymerize with more electron-rich olefins such as vinyl acetate for example. [80][81][82] Falireas et al 83 recently prepared amphiphilic diblock terpolymers composed of a PNIPAM or PDMA (DMA = N, N,-dimethyl acrylamide) hydrophilic block and an hydrophobic poly(MAF-TBE-alt VAc) block (MAFTBE = tertbutyl-2-trifluoromethacrylate) via sequential RAFT polymerization. Hydrolysis of the ester groups produced double hydrophilic diblock terpolymers endowed with pHresponsiveness (and also thermoresponsiveness for the PNIPAM-based BCP).…”
Section: -(Trifluoromethyl)acrylic Acid and Its Ester (Maf)mentioning
confidence: 99%